Outcomes of 219 chronic myeloid leukaemia patients with additional chromosomal abnormalities and/or tyrosine kinase domain mutations. (4th October 2018) - Xue, Mingming; Cheng, Juan; Zhao, Jiangyun; Zhang, Shuling; Jian, Jinli; Qiao, Yanhong; Liu, Bei
Abstract: Introduction: To confirm the role of additional chromosomal abnormalities (ACAs) and kinase domain (KD) mutations in the progression and outcomes of Chronic myeloid leukaemia (CML) patients and the connection between them, we analysed the ACAs and KD mutations of 219 CML patients admitted to our hospital. Methods: Cytogenetic analysis of metaphases was performed to detect ACAs, and the BCR‐ABL1 KD was sequenced to detect KD mutations. Results: Twenty‐four patients (11.0%) had ACAs in addition to the BCR‐ABL1 or t(9;22)(q34;q11) translocation. The most common abnormality was trisomy 8. Twelve different KD mutations were observed in 13 out of 53 imatinib‐resistant patients (24.5%). p.(Y235H) (n = 3; 23.07%), p.(F359V) and p.(T315I) (n = 2; 15.38%) presented most frequently. KD mutations subtypes (p.(E255K), p.(T315I), p.(F359V), p.(M244V) and p.(L298V)) coexisted with ACAs. The incidence of CML progression was 12/22 (54.5%) in the group of patients with ACAs and/or KD mutations and 2/143 (1.4%) in the group of patients without ACAs or KD mutations (CI 95%, P < 0.001) and was higher in the KD mutations group than in the ACAs group ( P = 0.046). The group of patients with ACAs and/or KD mutations had more men than the group of patients without ACAs or KD mutations ( P = 0.013). Conclusion: We conclude that ACAs and/or KD mutations are related to CML progression and are adverse outcome factors. Their presence exhibits gender differences and is more common in males. p.(E255K), p.(T315I), p.(F359V), p.(M244V) and p.(L298V) emerge more frequently when ACAs and KD mutations coexist.